Degradation of Oil Palm Empty Fruit Bunch (OPEFB) in Super-Critical Organic Solvents Affecting the Chemicals Distribution of Bio-Oil - Rakhman Sarwono; Saepulloh Saepulloh; Brayen Brayen; Andreas Andreas; Yeyen Maryani (Jurnal Kimia Terapan Indonesia, 2017)
Hydrothermal liquefaction (HTL) of oil palm empty fruit bunch (OPEFB) in different organic solvents (methanol, ethanol, acetone, toluene and hexane) to produce bio-oil were comparatively investigated. Experiments were carried out in an autoclave at different temperature of 300, 350 and 400 oC with a fixed solid/liquid ratio of 4 gram in 50 mL solvent, without catalysts and reaction time of 5 hours. The liquid products were analyzed using GCMS to determine the chemical composition. Result showed that the chemical compositions were greatly affected by the solvent types. Each solvent has a major component in bio-oil products. The major compounds resulted from methanol and ethanol solvent were ketones/others. The major compounds resulted from toluene and hexane solvents were organic acid, which favoured high temperature. Meanwhile, esters and organic acid were the major products from acetone solvents. Temperature operation resulted more variations in the chemical composition and the percentages of the bio-oil.